VARIABEL GURU IDEAL: SEBUAH TINJAUAN SISTEMATIS - Wahyuddin Wahyuddin (JPPI (Jurnal Pendidikan Islam Pendekatan Interdisipliner), 2022)
This systematic review aims to present variables that can be applied to attribute an excellent teacher. Moreover, it describes the difference of teacher criteria between the first-century (2000 and after) and pre-the-first-century (before the year of 2000). Peer-reviewed articles published in academic journals were searched on Google Scholar, Springer and Scopus by using search terms to find articles related to the systematic review purposes, which were “teacher characteristics”, “effective teacher”, “best teacher”, “teacher criteria”, “qualified teacher”, “21st century teachers”, “teacher quality” and "excellent teacher". The articles collected from the database were filtered based on eligibility criteria through the process of study selection. Results shows eleven included articles recorded in the databases. Such reports were reviewed to find out variables that they used to describe an ideal teacher. Moreover, the review was conducted based on other key features, namely number of publications, year of studies, number of citations, school level, countries of the studies, and variable distribution among the studies. It can be concluded that there are nine variables that can be used to describe an excellent teacher, which are content competency, pedagogical competency, kind characters, teaching principles, participation for positive changes, communication skills, self-improvement, experience and gender.